Cardiac Safety of Paclitaxel Plus Trastuzumab and Pertuzumab in Patients With HER2‐Positive Metastatic Breast Cancer. (16th March 2016) - Yu, Anthony F.; Manrique, Carlos; Pun, Shawn; Liu, Jennifer E.; Mara, Elton; Fleisher, Martin; Patil, Sujata; Jones, Lee W.; Steingart, Richard M.; Hudis, Clifford A.; Dang, Chau T.
Abstract : Introduction: Myocardial strain imaging and blood biomarkers have been proposed as adjuncts to left ventricular ejection fraction (LVEF) monitoring for the early detection of cardiotoxicity during cancer therapy. We report the results of a preplanned cardiac safety analysis of global longitudinal strain (GLS), and troponin‐I (TnI) and brain natriuretic peptide (BNP) levels in the phase II study of paclitaxel, trastuzumab, and pertuzumab (THP) for metastatic HER2‐positive breast cancer. Patients and Methods: Patients with 0–1 lines of prior therapy were treated with weekly paclitaxel (80 mg/m 2 ) plus trastuzumab (8 mg/kg loading dose followed by 6 mg/kg) and pertuzumab (840 mg loading dose followed by 420 mg) every 3 weeks. Exploratory endpoints were GLS measured with speckle‐tracking echocardiography every 3 months and TnI and BNP levels measured every 6 weeks (immediately pre‐ and postchemotherapy infusion) at 6 time points. Results: Sixty‐seven of 69 enrolled patients were treated with THP: 19 (28%) had hypertension, 8 (12%) had diabetes, 11 (16%) had hyperlipidemia, and 26 (38%) had smoking history. After a median follow‐up of 21 months (range: 3–38 months), no patients developed symptomatic heart failure. Two patients (3.0%) experienced asymptomatic LVEF decline (grade 2). The mean GLS (±SD) was 19% ± 2% (baseline), 19% ± 2% (month 6), and 19% ± 3% (month 12). Detectable TnI (>0.06 ng/mL) and elevated BNP (>100 pg/mL) levels were observed in 3 (4.3%) and 2 (3.0%) patients, respectively, but were not associated with LVEF decline. Conclusion: The absence of any significant changes in GLS and cardiac biomarkers (TnI and BNP) further support the cardiac safety of THP in patients with metastatic HER2‐positive breast cancer. Implications for Practice: Dual anti‐HER2 therapy with trastuzumab and pertuzumab in combination with taxane‐based chemotherapy improves overall survival in patients with metastatic HER2‐positive breast cancer. There is a critical need to investigate the potential cardiotoxicity of dual anti‐HER2 blockade, given the importance of HER2 signaling in cardiac homeostasis and stress response. Global longitudinal strain and cardiac biomarkers have been proposed as adjuncts to left ventricular ejection fraction for the early detection of cardiotoxicity. In this phase II study of combination trastuzumab and pertuzumab with paclitaxel, no clinically significant change was observed in global longitudinal strain or cardiac biomarkers. These results further support the cardiac safety of dual anti‐HER2 blockade previously reported in the CLEOPATRA study. The findings in the current study also call into question the role of intensive cardiac monitoring among patients treated with anti‐HER2 therapy in the absence of anthracyclines. Less frequent cardiac assessments could lead to a reduction in unnecessary treatment interruption and is an important consideration given the rise in medical expenditures, but this requires further investigation. Abstract : The results of a preplanned cardiac safety analysis of global longitudinal strain (GLS), and troponin‐I (TnI) and brain natriuretic peptide (BNP) levels in the phase II study of paclitaxel, trastuzumab, and pertuzumab (THP) for metastatic HER2‐positive breast cancer are reported. There were no statistically significant changes in GLS, and TnI and BNP levels. The finding supports the cardiac safety of THP in this group of patients.